Peran World Health Organization terhadap Krisis Kesehatan di Ukraina pada Masa Invasi Rusia Tahun 2022-2023 - Anisa Wanda Putri, M. Arsy Ash Ashiddiqy, Dani Kurniawansyah (Journal of Diplomacy and International Studies, 2022)
This article will discuss the role of the World Health Organization towards the health crisis in Ukraine during the Russian invasion in 2022-2023. The Russian invasion caused a humanitarian crisis, especially a health crisis. This research uses the concept of institutional liberalism as the main theory supported by the concepts of international organizations and human security. The method used is qualitative and the data obtained through literature study. The research found that WHO responded to the crisis in Ukraine, WHO acts as an instrument, arena and actor and carries out the functions of articulation aggregation, norms, recruitment, socialization, decision making and implementation, advocacy and operations.